Rare Earth Ions Adsorption onto Graphene Oxide Nanosheets. Issue 2 (23rd February 2017) - Ashour, Radwa M.; Abdelhamid, Hani Nasser; Abdel-Magied, Ahmed F.; Abdel-Khalek, Ahmed A.; Ali, M. M.; Uheida, A.; Muhammed, Mamoun; Zou, Xiaodong; Dutta, Joydeep
ABSTRACT: Graphene oxide (GO) was synthesized and used as a coagulant of rare earth elements (REEs) from aqueous solution. Stability and adsorption capacities were exhibited for target REEs such as La(III), Nd(III), Gd(III), and Y(III). The parameters influencing the adsorption capacity of the target species including contact time, pH, initial concentration, and temperature were optimized. The adsorption kinetics and thermodynamics were studied. The method showed quantitative recovery (99%) upon desorption using HNO3 acid (0.1 M) after a short contact time (15 min).